Methodological bases of estimating the efficiency of organizational and economic mechanism of regulatory policy in agriculture - N. Shibaeva; T. Baban; V. Prokhorova; O. Karlova; O. Girzheva; M. Krutko (Global Journal of Environmental Science and Management)
Ukrainian agriculture creates 12-14% of GDP. Ensuring the conditions for sustainable economic development implies the use of adequate mechanisms for regulating economic processes by the government. In the process of formation and implementation of the organizational and economic mechanism of regulatory policy, a system of indicators plays an important role in assessing the impact of such policy on the participants, monitoring and, in case of the deviation from planned results, adjusting regulatory measures. This research analyzes and systematizes the indicators that determine the organizational and economic mechanism of regulatory policy effectiveness in agriculture. The systematization of indicators to evaluate the organizational and economic mechanism of regulatory policy effectiveness in agriculture has allowed substantiating the methodological principles of its integrated assessment. Application of the proposed methodological approach to assessing the organizational and economic mechanism of regulatory policy effectiveness in agriculture in Ukraine was performed during 2010, 2016-2017 period. It revealed slow progress in the organizational and economic mechanism of regulatory policy efficiency during the investigated period. This result is primarily attributed to the lack of purposeful, systematic change management, the lack of mid-term planning, the strictness of most programs, imperfect financial instruments of the organizational and economic mechanism, and procedures for application.